ASSERTIVE LEXICON IN THE PUBLIC SIGNAGE OF DEMAK REGENCY: A LINGUISTIC LANDSCAPE EMPOWERMENT WITH EDUCATIONAL VALUE PERSPECTIVE - Mochamad Nuruz Zaman; Febrianus Rio Sasuwang; Mulyono (Program Studi Pendidikan Bahasa Inggris, 2025)
Effective public communication is a pillar of community empowerment and regional development. This community service research analyzes the assertive lexicon on public signage in Demak Regency, focusing on translational acceptability and its potential as a public education medium. The study reveals that while directive speech acts dominate the linguistic landscape, their English translations suffer from systemic acceptability issues, with an average score of only 2.0 (Less Acceptable). This deficiency hinders communicative functions and risks the normalization of linguistic errors. Based on these findings, a community empowerment program was designed and implemented in the form of a Workshop on Effective and Educative Public Sign Writing for local government agencies and business owners. The initiative bridges the gap between linguistic analysis and practical application, providing stakeholders with the tools to create a more inclusive and safe linguistic landscape, thereby supporting community empowerment and regional identity.